2020
DOI: 10.4085/1062-6050-478-18
|View full text |Cite
|
Sign up to set email alerts
|

When Should a Heat-Tolerance Test Be Scheduled After Clinical Recovery From an Exertional Heat Illness?

Abstract: Objective Researchers have produced a hypothesis of transient heat intolerance (HI) after exertional heat stroke (EHS). Based on this hypothesis, heat-tolerance testing (HTT) has been postponed until weeks 6 to 8 after EHS and other types of exertional heat illness (EHI). We compared the HTT results of participants after either EHS or other EHI who were tested earlier (≤6-week group) versus those who were tested later (>6-week group) to verify the hypothesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…However, individuals vary in their ability to tolerate heat stress and the inability to maintain thermal balance while exercising in a hot environment is known as heat intolerance [ 5 , 6 , 7 ]. Previous studies have reported that heat intolerance may be a by-product of inherent impaired thermoregulatory mechanisms or may occur as a direct result of exertional heat stroke (EHS) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals vary in their ability to tolerate heat stress and the inability to maintain thermal balance while exercising in a hot environment is known as heat intolerance [ 5 , 6 , 7 ]. Previous studies have reported that heat intolerance may be a by-product of inherent impaired thermoregulatory mechanisms or may occur as a direct result of exertional heat stroke (EHS) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, severe heat exposure and exhausting physical activity have a suppressant effect causing a temporary increase in susceptibility to infections and EHS [32]. Given that EHS may precede or accompany heat intolerance, it is essential to identify the biomarkers predictive of heat intolerance [14,33]. In the current study, there are significant differences in the baseline and post-test values for ALT, creatine kinase, creatinine and cortisol among the heat-intolerant group compared to the heat-tolerant group.…”
Section: Discussionmentioning
confidence: 99%
“…An important and frequently overlooked factor to consider with HTT is the fitness level of the individual. Most studies have only assessed HTT in well-trained athletes (including tactical), 4,8,21 even though individuals with lower physical fitness are at the greatest risk for EHS.…”
Section: Fitness Levelmentioning
confidence: 99%
“…30 Therefore, increased time between HTT trials or time spent in recovery from an EHS may result in loss of any potential heat acclimation or training adaptations already achieved. Additionally, while most research on HTT involves males, 4,8,21 emerging evidence suggests sex-dependent factors influence thermoregulation in general and heat acclimation adaptations specifically. As such, future HTT interpretations should consider potential sex and menstrual cycle phase differences.…”
Section: Heat Acclimationmentioning
confidence: 99%
See 1 more Smart Citation